Design and analysis of telecom service platform reconstruction based on open source software - Gang LU; Zhe WANG; Honghui OU; Zhenwei HE (Dianxin kexue)
Service platform reconstruction is an important part of the China Telecom network intelligent reconstruc-tion.Based on the analysis of network traffic problems,principle,architecture,and realization of open source of ser-vice network reconstruction were proposed.Reconstruction method was given by taking management platform as an example.Reconstruction requirements were researched from the point of view of open thinking,technology research and personnel construction.